Pengaruh Permasalahan Sosial Siswa Pindahan dan Dampaknya Terhadap Proses Belajar Mengajar Di SDN 014 Sangatta Selatan - Mohd. Samran; Muhammad Yasin (JURNAL ILMU PENDIDIKAN & SOSIAL (SINOVA), 2026)
This study aims to analyze the social problems experienced by transfer students and their impact on the teaching and learning process at SDN 014 Sangatta Selatan. The study employed a qualitative approach with data collection techniques consisting of interviews, observations, and documentation. The informants involved transfer students, teachers, the school principal, and parents. The results showed that transfer students faced various social problems, including difficulties adapting to a new environment, limitations in building social interactions, and feelings of isolation within the school environment. These social problems significantly affected the teaching and learning process, particularly in reducing students’ concentration, motivation, and participation in learning activities. The study also found that unfavorable social conditions could hinder students’ optimal learning achievement. In addition, the role of teachers and schools was found to be highly important in helping transfer students adapt through the creation of an inclusive, supportive, and conducive learning environment. The findings reinforce the view that successful learning is determined not only by academic aspects but also by the social and emotional support received by students. Therefore, holistic and sustainable learning strategies are needed by integrating social support into learning practices to improve both the quality of learning and the adaptation success of transfer students in the school environment.